A quick method to determine the impurity content in gold ornaments by LIBS technique - Haider, A F M Yusuf; Sengupta, S.; Abedin, K. M. (© 2015 SciTePress, 2017)
This conference paper was presented in the 3rd International Conference on Photonics, Optics and Laser Technology, PHOTOPTICS 2015; Berlin; Germany; 12 March 2015 through 14 March 2015 [© 2015 SciTePress] The conference paper's definite version is available at: 10.5220/0005249300410046